Studi Korelasi Karakteristik dan Status Gizi Ibu Hamil terhadap Prevalensi Stunting pada Balita - Enik Purwo Rahayu; Pintam Ayu Yastirin; Sehmawati Sehmawati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Monitoring nutritional status in 2018 reached 27.5% while the WHO limit was <20%. This means that approximately 8.9 million Indonesian children experience suboptimal growth, or 1 in 3 Indonesian children is stunted. More than one third of children under the age of 5 in Indonesia are below average in height. Purpose: To analyze the relationship between the health history of pregnant women and the incidence of stunting in the working area of the Responsibilityrjo Health Center. Methodology: The research design used is quantitative research using analytic survey methods with a cohort approach. The population is 3140 and the sample is 355 respondents. Results: The average respondent was 20-35 years old with a percentage of 80%, the education of the most respondents was high school with a total of 220 respondents or 62%. Most of the respondents' occupations were housewives, namely 102 respondents or 28.7% and the highest number of respondents were multigravidas, namely 215 or 60.6%. Health history of mothers during pregnancy with CED as many as 84 respondents (23.7%) and non-SEZ 271 mothers or 76.3% And mothers who experienced mild anemia were 98 mothers or 27.6% and mothers under five who experienced moderate anemia 22 respondents or by 6.2%, there were 135 stunted toddlers with a percentage of 38%, there was no relationship between age and work with stunting with a p value of maternal age of 0.611 and a p value of work of 0.158 and there was a relationship between education and parity most of the respondents were multigravida, namely 215 or 60.6%. Health history of mothers during pregnancy with CED as many as 84 respondents (23.7%) and non-SEZ 271 mothers or 76.3% And mothers who experienced mild anemia were 98 mothers or 27.6% and mothers under five who experienced moderate anemia 22 respondents or by 6.2%, there were 135 stunted toddlers with a percentage of 38%, there was no relationship between age and work with stunting with a p value of maternal age of 0.611 and a p value of work of 0.158 and there was a relationship between education and parity with the incidence of stunting, namely the p value Mother's education is 0.00 and the p value for mother's parity is 0.000. There is a relationship between maternal health history and the incidence of stunting. negative indicates that the better the mother's nutrition and the higher the mother's Hb, the lower the incidence. Suggestion: So that parents can better prepare for early pregnancy and pay more attention to their children's nutritional intake.